2013
DOI: 10.1186/ar4286
|View full text |Cite
|
Sign up to set email alerts
|

How do people with knee osteoarthritis use osteoarthritis pain medications and does this change over time? Data from the Osteoarthritis Initiative

Abstract: IntroductionThe aim of this analysis was to describe comprehensively the cross-sectional and longitudinal patterns of analgesic and nutraceutical medication use for knee osteoarthritis (OA) in a contemporary US cohort and to investigate associated demographic and clinical factors.MethodsBaseline, 12, 24 and 36 month data were obtained retrospectively from the National Institutes of Health Osteoarthritis Initiative. Participants had symptomatic radiographic knee OA. Multiple binary logistic regression models id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 36 publications
10
83
2
2
Order By: Relevance
“…Recommendation of weight loss and exercise was low, suggesting a focus on pharmacotherapies [37]. These findings are generally in line with other studies suggesting that pharmacological therapies are used more frequently in this population [35,36]. Previous studies have indicated that advice on weight loss is given to less than half of obese adults with arthritis [37,38].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recommendation of weight loss and exercise was low, suggesting a focus on pharmacotherapies [37]. These findings are generally in line with other studies suggesting that pharmacological therapies are used more frequently in this population [35,36]. Previous studies have indicated that advice on weight loss is given to less than half of obese adults with arthritis [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…Notably, a similar proportion reported being in constant pain despite medication, suggesting a perception that treatment will only partially relieve symptoms [30]. Prescribed medications were used by two thirds of respondents and use of OTC medications was in line with previous studies, with GPs generally aware of this use [35,36]. Irregular use of medication was common, and in line with previous reports, highlighting the previously reported perception that individuals are concerned about developing tolerance to medications and only using medication when really needed.…”
Section: Discussionsupporting
confidence: 69%
“…The presence of pain and joint stiffness are important contributors to a diminished health-related quality of life, and nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most commonly prescribed drugs (58Á9% of all prescriptions) in the treatment of OA [43].…”
Section: Medication Use Role Of Nonsteroidal Anti-inflammatory Drugsimentioning
confidence: 99%
“…The optimal treatment for people with OA combines pharmacological and non-pharmacological treatments 4. Non-steroidal anti-inflammatory drugs (NSAIDs) and selective cyclo-oxygenase-2 inhibitors are the most commonly used painkillers for people with OA in Europe and the USA, with 20% to 35% of the OA population reporting their use 5 6…”
Section: Introductionmentioning
confidence: 99%